Violation of children's and adolescents' rights - the profile of a southern state in Brazil - Mariucha Ramella Marcon Nemer; Bruna de Souza Nogueira; Fernanda do Nascimento de Lemos Campos; Márcia Cristina da Silva; Morgana Ducatti Alves; Luiz Fernando Lolli (Universidade Estadual de Maringá, 2020)
The rights of children and adolescents are provided by law and it is the duty of the State, family and society to care for them. Health and education professionals are responsible for reporting suspected or confirmed cases of rights violation. This study aimed to investigate the prevalence and qualification of violation of children's and adolescents' rights in the State of Paraná between 2009 and 2014. A descriptive and observational quantitative study was carried out based on the records of the Child Protective Services in Paraná, accessed through the Information System for Childhood and Adolescence (SIPIA). A total of 129.123 violations of rights were found. Among those cases, the right to familiar and communitarian companionship stands out with the greatest number of violations, followed by the right to education, culture, sports and leisure. Mothers were found to be the main aggressors, followed by fathers, and sexual violence/abuse was the most prevalent type of violence. In conclusion, there was a significant amount of violation of children's and adolescents' rights in the State of Paraná during the period covered by this research, and it has increased over the years. Besides, we found out that there is a predisposition of gender and age group for each variable analyzed.